2018
DOI: 10.1111/bjhp.12317
|View full text |Cite
|
Sign up to set email alerts
|

What are the ‘active ingredients’ of interventions targeting the public's engagement with antimicrobial resistance and how might they work?

Abstract: ObjectivesChanging public awareness of antimicrobial resistance (AMR) represents a global public health priority. A systematic review of interventions that targeted public AMR awareness and associated behaviour was previously conducted. Here, we focus on identifying the active content of these interventions and explore potential mechanisms of action.MethodsThe project took a novel approach to intervention mapping utilizing the following steps: (1) an exploration of explicit and tacit theory and theoretical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…The Theoretical Domains Framework (TDF) can be considered an elaboration of COM-B (see Table S1). McParland [21] used the TDF and the Behavior Change Technique (BCT) Taxonomy version 1 (BCTTv1) [22], a classification of "active ingredients" that are used to change behavior, to describe public awareness AMR interventions. The authors concluded that there is a clear potential for improvement of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The Theoretical Domains Framework (TDF) can be considered an elaboration of COM-B (see Table S1). McParland [21] used the TDF and the Behavior Change Technique (BCT) Taxonomy version 1 (BCTTv1) [22], a classification of "active ingredients" that are used to change behavior, to describe public awareness AMR interventions. The authors concluded that there is a clear potential for improvement of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Again long-term outcomes were not examined. Although only four of the studies reported any explicit theoretical basis (two social marketing theory; two 'precede-proceed' model), intervention descriptions revealed that all included at least one behavioral change technique [19]. The most common of these focused on educating participants about the consequences of behavior and using a trusted source of information to instruct participants on how to perform AMR-related behaviors.…”
Section: Interventionsmentioning
confidence: 99%
“…Not until recent years did researchers systematically report efforts in the identification of the root causes of operational barriers and facilitators in designing, implementing, and evaluating interventions. For instance, in 2018 and 2019, Langdridge et al have attempted to decipher the intervention elements and visual imagery used in public antimicrobial stewardship [23,103].…”
Section: Relation To Other Studiesmentioning
confidence: 99%